Plastic waste reduction through catalyzing motivational factors: Implications for sustainable development goals in emerging economies - Taqi, Hasin Md Muhtasim; Salman, Sheak; Ahmed, Sayem; Taghipour, Amirhossein; Mazumder, Nirjhar; Ali, Syed Mithun (My University, 2025)
Plastic pollution is increasingly recognized as a global crisis, driven by excessive production, consumption, and careless disposal of plastic materials. As plastic pollution endangers the environment, animal life, and human health, global awareness is growing. Unanticipated growth in plastic waste poses a grave threat to emerging economies. Hence, all members of the plastic value chain are required to contribute to the reduction of plastic waste. Therefore, this study aims to identify and analyze the motivational factors influencing stakeholders' decisions to decrease their plastic consumption in emerging economies. Utilizing a combination of Single-Valued Neutrosophic (SVN) approaches and the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method, the most crucial factors are identified. The finding shows that, “internal motivators” is the most important context and in this context, “pressure from investors and shareholders for manufacturing sustainable products” and “demoralizing single-use plastic” are the most influential motivational factors for reducing plastic waste. The findings have implications for consumers, businesses, and policymakers. Through an awareness of these motivating factors, stakeholders can put specific initiatives into place to encourage a sustainable culture and reduce the detrimental impacts of plastic pollution on the environment and society. Overall, this study offers a thorough framework for dealing with plastic waste in emerging economies, directing future efforts towards practical solutions.
Keywords: Decision-making trial and evaluation laboratory; Motivational factors; Plastic waste; Single valued neutroshopic set